THE APPLICATION OF ALTERNATIVE DISPUTE RESOLUTION IN CONSUMER DISPUTE RESOLUTION BASED ON LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION: PENERAPAN ALTERNATIVE DISPUTE RESOLUTION DALAM PENYELESAIAN SENGKETA KONSUMEN BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Wirotomo, Heristiawan Aryo; Marsudi Dedi Putra (Asosiasi Dosen Hukum Acara Perdata (ADHAPER), 2025)
Consumer dispute resolution in Indonesia is explicitly regulated under Law Number 8 of 1999 concerning Consumer Protection, which provides space for non-litigation settlement through Alternative Dispute Resolution (ADR). The application of ADR, particularly through the Consumer Dispute Settlement Agency (BPSK), reflects the implementation of the principle of fast, simple, and low-cost justice as mandated in Article 2 paragraph (4) of Law Number 48 of 2009 on Judicial Power. This research employs a normative legal method with a statute approach and a conceptual approach. Data were obtained from literature studies covering legislation, legal doctrines, and relevant court decisions. The results of the study indicate that ADR through BPSK serves as an effective mechanism to provide legal certainty, protect consumer rights, and ensure access to justice, particularly for consumers harmed by business actors. However, the effectiveness of ADR still faces several challenges, including limited human resources, low consumer awareness of ADR mechanisms, and the emerging complexity of disputes in the digital trade sector (e-commerce). Therefore, strategies to improve BPSK’s performance are required through regulatory optimization, the use of digital technology in dispute resolution, and capacity building of human resources, so that ADR mechanisms can become more adaptive, responsive, and relevant to the dynamics of consumer protection in Indonesia.